WHAT MAKES EFL SPEAKERS’ UTTERANCES MORE INTELLIGIBLE IN THE CONTEXT OF GLOBAL INTELLIGIBILITY? - Moedjito, M.; Jaelani, Selamet Riadi; Asrobi, Maman (Indonesian Journal of Applied Linguistics, 2019)
In this globalisation era, native-like pronunciation has no longer become the goal of pronunciation teaching in EFL classrooms. Instead, intelligibility, more specifically, global intelligibility, has become a legitimate goal of pronunciation teaching (Moedjito, 2009). However, researchers and practitioners have not reached to the final conclusion of what makes EFL speakers? utterances more intelligible. This paper is to report a study investigating factors which made EFL speakers? utterances more intelligible in the context of global intelligibility. In order to achieve the goal, the present researchers used three instruments to collect data: a questionnaire, an in-depth interview, and an assessment of EFL speakers? utterances from the in-depth interview. The quantitative data from the questionnaire and assessment of EFL speakers? utterances were submitted to a Pearson?s Product Moment test to assess the correlation coefficient of each independent variable to intelligibility and to a multiple regression test to examine the predictive power of the independent variables to intelligibility as the dependent variable. Meanwhile, the data of the in-depth interview were qualitatively scrutinised. The results of the data analysis revealed that word pronunciation accuracy might become the most influencing factor which made EFL speakers? utterances more intelligible. In addition to the accurate pronunciation, meaningful vocabulary might crucially account for intelligibility of EFL speakers? utterances. These findings were positively confirmed by the results of the in-depth interview analysis. The major pedagogical implication of the study is that in English pronunciation classes, there should be more focus on word pronunciation accuracy in EFL classrooms.